PREVENTION OF FRAUD IN GOVERNMENT PROCUREMENT OF GOODS AND SERVICES WITH E-CATALOG IMPLEMENTATION - Juherman, Baso (Universitas Airlangga, 2025)
Supporting government functionality requires extreme attention, especially to provide services to the society in which the government is responsible of . The efficiency and effectiveness of government services to the society can be done extensively by acquiring favor from the other government agency or any third party offering their services. However this could be obtained by procuring goods and services. The procurement of goods and services is a procurement activity conducted by the government agency using the national budget. The procurement is carried out in public to ensure there is no collusive action to arbitrarily earn the procurement, resulting in losses to the government and society. However, there are many collusive actions carried out throughout the procurement process in Indonesia. The government develops E-Catalog for procurement of goods and services to mitigate those collusive actions. The research will try to analyze the effectiveness of the E-Catalog to prevent any fraud on the procurement of goods and services process. The results of this study indicate that the procurement of goods and services electronically is designed to manage the procurement of goods and services in a more transparent, effective and efficient manner, using the Electronic Procurement Service (LPSE), but the regulation is still not specific, both in terms of substance and technicality, so it feels not yet effective.